Discovery of ordered tetragonal and cubic phases in the morphotropic phase boundary region of (1-x)Bi(Mg3/4W1/4)O3-xPbTiO3 piezoceramics - Verma N.K.; Singh A.K. (My University, 2025)
Studies on (1-x)[Bi(Mg3/4W1/4)O3]-xPbTiO3 ceramics across morphotropic phase boundary have been done to investigate the crystal structure and structure-property correlations. Rietveld structure refinement reveals that the structure of the morphotropic phase boundary compositions consists of coexisting ordered tetragonal and cubic phases for 0.55 < x < 0.72, not reported earlier. The structure is B-site ordered cubic (space group Fm-3m) for the compositions with x ≤ 0.55, B-site ordered tetragonal (space group I4/m) for x ≥ 0.72. The structure gradually transforms into disordered tetragonal phase (space group P4mm) for higher concentrations (x) of PbTiO3. Raman studies also confirm the B-site ordered structure for the compositions close to morphotropic phase boundary. For all the compositions investigated, two peaks are observed in the temperature dependence of the permittivity, originating due to dielectric relaxation and structural transition from tetragonal (I4/m) to cubic (Fm-3m) phase. A new phase diagram of the solid solution is established. © 2019 Elsevier Ltd and Techna Group S.r.l.